2022
DOI: 10.1186/s12883-022-02641-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients with degenerative cervical myelopathy exhibit neurophysiological improvement upon extension and flexion: a retrospective cohort study with a minimum 1-year follow-up

Abstract: Background Cervical extension and flexion are presumably harmful to patients with degenerative cervical myelopathy (DCM) because they worsen medullary compression visible on dynamic magnetic resonance imaging (MRI). Dynamic somatosensory evoked potentials (SSEPs) are an objective tool to measure the electrophysiological function of the spinal cord at different neck positions. In contrast to previous hypotheses, a considerable proportion of patients with DCM present improved SSEPs upon extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…They concluded that cervical motion would worsen the course of CSM, whatever the severity of the patient was. However, a recent retrospective study reported neurological improvement upon extension and flexion in CSM patients [38]. This study reported a significant DSSEP improvement, which is a subjective neurophysiological indicator of the spinal cord, in 18% and 22% of patients during extension and flexion, respectively.…”
Section: Dynamic Factorsmentioning
confidence: 59%
“…They concluded that cervical motion would worsen the course of CSM, whatever the severity of the patient was. However, a recent retrospective study reported neurological improvement upon extension and flexion in CSM patients [38]. This study reported a significant DSSEP improvement, which is a subjective neurophysiological indicator of the spinal cord, in 18% and 22% of patients during extension and flexion, respectively.…”
Section: Dynamic Factorsmentioning
confidence: 59%
“…The intrinsic mechanism by which dynamic DTI parameters can be evaluated for their postoperative and predictive value may be as follows: in the extension cervical position, the ligamentum avum is anteriorly convex, the spinal canal is narrowed, the longitudinal length and stretch of the cervical cord are reduced, the dorsal subarachnoid space is reduced, and it is susceptible to circumferential pressure; in the exion cervical position, the ligamentum avum is stretched, which increases the longitudinal strain of the spinal cord and results in spinal decompression and improved function, and the dorsal subarachnoid space increases and it is susceptible to anterior pressure. It demonstrated that intramedullary T2WI intensity was maximal compared to the natural neck position and extended neck position [17,18] . Flexion causes anterior and posterior spinal artery compression, decreasing blood supply; extension relieves vascular compression axonal injury within the spinal cord, increases membrane permeability, and leads to loss of conduction in myelinated axons [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were younger than 18 years old on the index date were excluded. To preserve sufficient follow-up and quality of the included data, we followed the inclusion and exclusion criteria used by Kanwal et al [31], and we thus excluded those patients with less than 5 years of data in the Cerner Health FactsÒ database after the index bias introduced by this exclusion criteria will have minimal impact on our method evaluation and is outweighed by the benefit of resulting high quality data as demonstrated by many studies [31][32][33][34]. We excluded patients with hepatitis B or hepatitis C virus to eliminate the impact of these well-known risk factors for HCC.…”
Section: Study Cohortsmentioning
confidence: 99%
“…Pretrain from scratch Finetune the model pretrained by case-control set date of NAFLD. Since the data is used to evaluate both baseline and deep learning methods, any bias introduced by this exclusion criteria will have minimal impact on our method evaluation and is outweighed by the benefit of resulting high quality data as demonstrated by many studies [31][32][33][34]. We excluded patients with hepatitis B or hepatitis C virus to eliminate the impact of these well-known risk factors for HCC.…”
Section: Disease Prediction Model For Hccmentioning
confidence: 99%